The captive brides collection [large type] : 9 stories of great challenges overcome through great love - AlLee, Jennifer; Breidenbach, Angela; Davis, Susan Page; Franklin, Darlene; Hall, Patty Smith; Hickey, Cynthia; Pagels, Carrie Fancett; Thompson, Lucy; Welborn, Gina (Thorndike Press, 2018)
Journey through history as nine women make their escapes from some of life's greatest challenges. West Indies, 1655: Temperance only wanted a better life. Instead, she's sold as an indentured servant. Atlantic Ocean, 1755: Charlotte is deported to the British colonies for her father's crimes. Virginia, 1850: With her life in peril, Lettie seeks escape from slavery. Barbary Coast, 1873: Goldie must pay the cost of her upbringing--or work at her guardian's brothel. Can these captive hearts, and five others, be freed to dream, to dare, to love?